Research on the Effect of Executive Team Heterogeneity on ESG Performance - Li, Kexin (Transactions on Economics, Business and Management Research, 2024)
In recent years, the ESG performance of firms has attracted considerable attention from both academia and the practical field. Enhancing firms' ESG performance not only serves as a “wind vane” for sustainable development but also injects new vitality into the high-quality growth of China’s economy. As the core actors within the corporate power hierarchy, the heterogeneity characteristics of the executive team are significant determinants of corporate behavior and may influence firms' ESG performance. Based on Corporate Life Cycle Theory and Upper Echelons Theory, this paper empirically tests the relationship between executive team heterogeneity and firms' ESG performance using the data from Chinese A-share listed companies for the period 2009-2021. The empirical results reveal that age heterogeneity and financial background heterogeneity in the executive team have significant negative effects on firms' ESG performance; in contrast, executive team academic background heterogeneity significantly enhances firms' ESG performance.The mechanism test indicates that the quality of accounting information disclosure plays a partial mediating role in the relationship between executive team heterogeneity and firms' ESG performance. Further analysis shows that the effect of executive team heterogeneity on firms' ESG performance is more pronounced in corporates that are in the mature and decline stages. This study enriches the research on the economic consequences of executive team heterogeneity and the influencing factors of firms' ESG performance, providing theoretical support and empirical evidence for promoting sustainable development and deeply implementing the "Dual Carbon" goals.